The histopathology of pathergy: a chronologic study of skin hyperreactivity in Behcet's disease - ERGUN, SAFİYE ATLAS TÜLİN (BLACKWELL SCIENCE LTD, 1998)
Background many patients with Behcet's disease (BD) demonstrate hyperreactivity (pathergy), and the induced skin lesions may serve as a model for the disease. Objective This study examined the sequence of histopathologic changes after needle prick trauma. Methods Eight patients fulfilling the International Study Group Criteria for Behcet's Disease, two patients with recurrent aphthous stomatitis, and two healthy controls each underwent intradermal injections with subsequent biopsies at 0, 4, 24, and 48 h. Hematoxylin and eosin sections were evaluated in a blinded fashion according to 11 histopathologic criteria. Results At time zero, normal skin was seen. By 4 h, neutrophils were present usually admired with lymphocytes (8 out of 10). The inflammatory cell density peaked by 24 h in 8 out of 10 patients and at 48 h in 2 out of 10 patients. Sparse leukocytoclasis was identifiable from 4 to 48 h, but was not associated with fibrin, True vasculitis (as evidenced by fibrin within vessel walls and/or intraluminal thrombi) was not seen, Intraepidermal pustules (IEPs) and polymorphonuclear (PMN) aggregates within the needle tract were seen as early as 4 h. The control patients and three out of eight of the ED patients failed to develop clinical lesions. Among this group histopathologic IEPs were lacking in all but two ED patients. Conclusions These data suggest that early pathergy is mediated by PMNs and lymphocytes without vasculitis. Hyperchemotaxis may explain the rapid accumulation of PMNs along the injection site.
Keywords: LESIONS; IMMUNOHISTOLOGY